"Moving" the Pyramids of Giza: Measuring the Effects of Ethics Education in a Visual Communication Curriculum. Issue 1 (2nd January 2016) - Dahmen, Nicole Smith
Abstract : As mass communication scholars and educators, we should be greatly concerned about how we teach ethics to our students. This research posits improving the quality of mass communication education with the intention of producing top-notch journalists who are dedicated to raising the credibility of the profession. Specifically, the research assesses the effects of integrating ethical content within a visual communication course, focusing on two critical and timely issues in visual journalism: the acceptability of graphic photographs and image manipulation. Findings showed significant differences in how participants viewed selected ethical issues in visual journalism from time 1 to time 2 .